Finnish Reforms of Procedural Law: A Success Story? - Johanna Niemi (Social Sciences Academic Press, 2025)
The Finnish law on court proceedings was totally reformed in the 1990s. The antiquated quasi-oral unstructured proceedings dating from 1734 were transformed into a modern trial model. Civil procedures at first instance were reformed first, with the slogan of orality, concentration and immediacy of trial. These three principles refer to the main hearing of the trial, which thus structures the whole process. The reform has in many ways been a success from which other countries may take lessons. However, reasonable time and costs still remain a challenge. The article reviews the Finnish reform process of civil procedure at first instance.
Rule of Law Development and Judicial Reform: A Comparison Between China and Finland